Factors influencing in-hospital delay in treatment with intravenous thrombolysis - Mikulík, Robert; Kadlecová, Pavla; Czlonkowska, Anna; Kobayashi, Adam; Brozman, Miroslav; Svigelj, Viktor; Csiba, Laszlo; Fekete, Klara; Kõrv, Janika; Demarin, Vida; Vilionskis, Aleksandras; Jatuzis, Dalius; et al. (Stroke, 2012)
BACKGROUND AND PURPOSE: Shortening door-to-needle time (DNT) for the thrombolytic treatment of stroke can improve treatment efficacy by reducing onset-to-treatment time. The goal of our study was to explore the association between DNT and outcome and to identify factors influencing DNT to better understand why some patients are treated late. METHODS: Prospectively collected data from the Safe Implementation of Treatments in Stroke-East registry (SITS-EAST: 9 central and eastern European countries) on all patients treated with thrombolysis between February 2003 and February 2010 were analyzed. Multiple logistic regression analysis was used to identify predictors of DNT ≤ 60 minutes. RESULTS: Altogether, 5563 patients were treated with thrombolysis within 4.5 hours of symptom onset. Of these, 2097 (38%) had DNT ≤ 60 minutes. In different centers, the proportion of patients treated with DNT ≤ 60 minutes ranged from 18% to 84% (P<0.0001). Patients with longer DNT (in 60-minute increments) had less chance of achieving a modified Rankin Scale score of 0 to 1 at 3 months (adjusted OR, 0.86; 95% CI, 0.77-0.97). DNT ≤ 60 minutes was independently predicted by younger age (in 10-year increments; OR, 0.92; 95% CI, 0.87-0.97), National Institutes of Health Stroke Scale score 7 to 24 (OR, 1.44; 95% CI, 1.2-1.7), onset-to-door time (in 10-minute increments; OR, 1.19; 95% CI, 1.17-1.22), treatment center (P<0.001), and country (P<0.001). CONCLUSIONS: Thrombolysis of patients with older age and mild or severe neurological deficit is delayed. The perception that there is sufficient time before the end of the thrombolytic window also delays treatment. It is necessary to improve adherence to guidelines and to treat patients sooner after arrival to hospital.
Keywords: Humans; lidé středního věku; Stroke; Guideline Adherence; Nervous System Diseases; Thrombolytic Therapy; trombolytická terapie; Aged; Female; věkové faktory; senioři; lidé; hospitalizace; časové faktory; cévní mozková příhoda; ženské pohlaví; dodržování směrnic; Hospitalization; Male; Middle Aged; nemoci nervového systému; Age Factors; mužské pohlaví; prospektivní studie; Time Factors; Prospective Studies